Domestic cat paraplegia compatible with Gurltia paralysans nematode. First cases reported in Colombia (2011)
ABSTRACT: Six cases of cat paraplegia diagnosed in years 2001 and 2002 in Antioquia province (Colombia) are reported in this paper. Diagnosis was supported on clinical exams, radiography, myelogram, necropsy, and histopathology. Clinical signs where ataxia, decreased superficial sensitivity, loss of deep sensitivity, progressive paralysis, hind limb atrophy, and urinary and fecal retention. Necropsy and histopathology analysis revealed the presence of a nematode in the spinal cord meningeal blood vessels at the T10-L4 segment level, causing medullar compression and myelomalacia. Differential diagnose was conducted through the analysis of the parasite’s histopathological cuts. Its morphological characteristics differed from those of other possible nematodes such as filarial erratic larve, Ancylostome sp, and Ascaris sp. It was concluded that the nematode is compatible with the one described as Gurltia paralysans.